2014
DOI: 10.1088/0031-8949/89/8/084001
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in binary microlensing events

Abstract: The light received by source stars in microlensing events may be significantly polarized if both an efficient photon scattering mechanism is active in the source stellar atmosphere and a differential magnification is therein induced by the lensing system. The best candidate events for observing polarization are highly magnified events with source stars belonging to the class of cool, giant stars in which the stellar light is polarized by photon scattering on dust grains contained in their envelopes. The presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It shows that the source crossed the tip of the caustic. We note that finite-source effects could also have been detected through specific features of polarization curves, if a polarization observation of the event were conducted (Ingrosso et al 2012(Ingrosso et al , 2014.…”
Section: Discussionmentioning
confidence: 93%
“…It shows that the source crossed the tip of the caustic. We note that finite-source effects could also have been detected through specific features of polarization curves, if a polarization observation of the event were conducted (Ingrosso et al 2012(Ingrosso et al , 2014.…”
Section: Discussionmentioning
confidence: 93%
“…If it is so, it will be the first exoplanet in another galaxy [44][45][46][47]. As it was noted [48][49][50] polarization observations for pixel lensing event play an extremely important role to clarify parameters of microlenses and sources which are giant stars for pixel lensing events (see also [51] for a review).…”
Section: Gravitational Lensingmentioning
confidence: 99%
“…It has been shown that polarization measurements could resolve degeneracies in theoretical models of microlensing events [85]. Calculations of polarization curves for microlensing events with features in the light curves induced by the presence of an exoplanet and observed towards the Galactic bulge have been done [87,88,89,90,91]. We use simple polarization and limb darkening models developed by [92], however, improved models are also developed taking into account radiative transfer in spectral lines, see for instance simulation results developed for Sun [93].…”
Section: Polarization Curves For Microlens Systems With Exoplanetsmentioning
confidence: 99%